INTERACTIVE LEARNING TECHNOLOGIES IN HIGHER EDUCATION AS A TOOL FOR TRAINING A COMPETITIVE SPECIALIST - О. Bieliaieva; Т. Skrypnikova; Т. Khmil (Проблеми екології та медицини)
The article analyzes the views of Ukrainian and foreign researchers on interactive learning. The main interactive technologies common in educational practice are briefly characterized. The conclusions state that the widest possible use of interactive technologies in the educational process at medical universities is a necessary condition for the training of competitive specialists in the field of health care at the undergraduate and postgraduate stages, as well as in the process of further continuous professional development of doctors. A defining feature of interactive learning is creative, constant and effective communication between the subjects of the educational process and the presence of constructive feedback between them. The main advantages of interactive learning are the ability to: level the contradiction between motivation and stimulation in the learning process, static and dynamic learning; form the future doctors' awareness of the importance and value of various types of communication; simulate professional situations, solving which students can demonstrate the acquired knowledge, abilities and skills in a relaxed and psychologically comfortable atmosphere, which encourages them to actively participate in all stages of an interactive class; solve real cases from medical / dental practice; implement formative assessment; regulate inter-subject relationships in the educational process; develop clinical thinking, the ability to substantiate one's own opinion and the ability to defend one's own position, critically evaluate adopted and propose alternative solutions, teamwork skills, communicative culture, positive motivation, and self-confidence.